Job Satisfaction among Academic Staff in TVET Institutions - Mohammad Fardillah Wahi; Habsah Mohamad Sabli; Sari Lestari Zainal Ridho (International ABEC, 2021)
The scenario of the Covid 19 pandemic and movement control order (MCO) force closing all the higher institutions in Malaysia. Due to this situation, online learning implements by educators at home plus household matter demotivated and lead to a decrease in job satisfaction. Therefore, the purpose of this study to identify the relationships concerning recognition, promotion and also to identify if there exists a differences job satisfaction of male and female among academic staff in Politeknik Sarawak which include Politeknik Kuching Sarawak (PKS), Politeknik Mukah Sarawak (PMU) and lastly Politeknik Metro Betong (PMB). Data was collected from 324 academic staff and analyzed using correlation and Mann-Whitney U test analysis. There is a significant relationship between promotion with job satisfaction compared to recognition. The female consists of (48.1%), and male (51.9%). Only the recognitions have significantly corelated with job satisfaction compare to promotions. Based on the Mann- Whiney U test there is no different of job satisfactions between genders. This outcome of this research can benefit the decisionmakers such as governments, institutions, and policymakers to give suitable recognition and promotion to educators to enhance their job satisfaction.